Microstructure and properties of intercritically reheated coarse-grained heat affected zone in pipeline steel after secondary thermal cycle. (29th July 2021) - Han, Yongdian; Fei, Jiyuan; Xin, Ping; Wang, Ruizhe; Jing, Hongyang; Zhao, Lei; Xu, Lianyong
Abstract: As a kind of high strength microalloyed steel, pipeline steel has high strength and toughness. However, the formation of the intercritically reheated coarse-grained heat affected zone (ICCGHAZ) during the welding process is an important limitation affecting its performance. Herein, microstructural transformation in the ICCGHAZ of X100 pipeline steel after a secondary thermal cycle and hydrogen sulfide stress corrosion cracking (SSCC) resistance of the transformed microstructure are investigated. The microstructure of X100 pipeline steel after the secondary thermal cycle is similar to that after the primary thermal cycle, comprising lath bainite and granular bainite. With an increase in t8/5 (time required for the material to cool from 800 °C to 500 °C), the M-A constituents that continuously precipitate along the prior austenite grain boundaries in the second thermal cycle are coarsened and form a necklace-type structure. A variation in t8/5 does not significantly affect the crystallographic characteristics of the ICCGHAZ. The stress corrosion test shows that the resistance to SSCC decreases and cleavage fracture characteristics become more noticeable with an increase in t8/5 . Graphical abstract: Image 1 Highlights: The microstructure of the ICCGHAZ in X100 pipeline steel changes little with the increase of t8/5 . M-A constituents in the ICCGHAZ coarsen and form necklace-type structure. SSCC resistance decreases with the increase of t8/5 . The crystallographic characteristics have relatively little effect on SSCC sensitivity.